Efektivitas Penggunaan Media Quizizz dalam Meningkatkan Hasil Belajar Siswa terhadap Struktur dan Kaidah kebahasaan Teks Diskusi di Kelas IX-8 SMP Negeri 8 Medan - Arzety, Yunda Elza; Ali, Ali; Evita, Evita (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study investigates the effectiveness of integrating Quizizz as a digital learning medium to enhance students’ mastery of structural and linguistic features in discussion texts, specifically targeting Class IX-8 students at SMP Negeri 8 Medan. Employing a Classroom Action Research (CAR) design with both quantitative and qualitative approaches, the study involved 31 students whose learning outcomes were evaluated through formative assessments, observations, and student response questionnaires. Prior to the intervention, the average pre-test score was 86.2, with 67.7% of students scoring ?85. Following the implementation of Quizizz across learning cycles, the average post-test score rose to 92.5, with 71% scoring ?90. In the experimental setting, scores further improved to an average of 93.6, with 83.9% of students attaining ?90. Survey results revealed that 77.4% of students believed Quizizz enhanced their understanding of the material, while 90.3% appreciated its real-time feedback. The gamified elements of Quizizz—such as point systems and leaderboards—were shown to increase motivation and foster a more interactive, engaging learning experience. The findings underscore Quizizz’s potential as an effective digital tool to support academic achievement in language learning, particularly in the context of discussion text writing.